Answer: 6
Step-by-step explanation:
176282836287262727277336 don’t listen to this answer
Answer:
The length is 5.5 inches
Step-by-step explanation:
The area of a rectangle is
A = lw
66 = l * 12
Divide each side by 12
66/12 = l
5.5 = l
The length is 5.5 inches
Answer:
![(f+g)(2) = 14](https://tex.z-dn.net/?f=%28f%2Bg%29%282%29%20%3D%2014)
![f(g(x)) = 2x^2 + 4x +3](https://tex.z-dn.net/?f=f%28g%28x%29%29%20%3D%202x%5E2%20%2B%204x%20%2B3)
![\frac{f(x)}{g(x)} = \frac{2x+1}{x^2+2x+1}](https://tex.z-dn.net/?f=%5Cfrac%7Bf%28x%29%7D%7Bg%28x%29%7D%20%3D%20%5Cfrac%7B2x%2B1%7D%7Bx%5E2%2B2x%2B1%7D)
![f(2) + g(-2) = 6](https://tex.z-dn.net/?f=f%282%29%20%2B%20g%28-2%29%20%3D%206)
Step-by-step explanation:
Function composition and transformation combines functions together using operations such as addition, subtraction, multiplication, division and substitution. To find each, perform the operation with the functions f(x) = 2x+1 and
.
(f+g)(x) is the functions f and g added together with 2 substituted for x.
![(f+g)(x) = 2x+1 + x^2 +2x + 1 = x^2 + 4x + 2\\(f+g)(2) = 2^2 + 4(2) + 2 = 14](https://tex.z-dn.net/?f=%28f%2Bg%29%28x%29%20%3D%202x%2B1%20%2B%20x%5E2%20%2B2x%20%2B%201%20%3D%20x%5E2%20%2B%204x%20%2B%202%5C%5C%28f%2Bg%29%282%29%20%3D%202%5E2%20%2B%204%282%29%20%2B%202%20%3D%2014)
(f·g)(x) is function composition that means f(g(x)) or substitute g(x) into f(x).
![f(g(x)) = 2(x^2+2x+1)+1 = 2x^2 + 4x+2 + 1\\f(g(x)) = 2x^2 + 4x +3](https://tex.z-dn.net/?f=f%28g%28x%29%29%20%3D%202%28x%5E2%2B2x%2B1%29%2B1%20%3D%202x%5E2%20%2B%204x%2B2%20%2B%201%5C%5Cf%28g%28x%29%29%20%3D%202x%5E2%20%2B%204x%20%2B3)
f(x) / g(x) is division of the two functions. Division can only occur with polynomials if they share the same factors or things which multiply to create them. If none are present, do not simplify.
![\frac{f(x)}{g(x)} = \frac{2x+1}{x^2+2x+1}](https://tex.z-dn.net/?f=%5Cfrac%7Bf%28x%29%7D%7Bg%28x%29%7D%20%3D%20%5Cfrac%7B2x%2B1%7D%7Bx%5E2%2B2x%2B1%7D)
This cannot be simplified.
f(2) + g(-2) means find the function value of f at 2 and the function value of g at -2 then add them together.
![f(2)+g(-2) = 2(2)+1 + ((-2)^2+2(-2) + 1)\\f(2) + g(-2) = 5 + (4-4+1)\\f(2) + g(-2) = 5 +1 = 6](https://tex.z-dn.net/?f=f%282%29%2Bg%28-2%29%20%3D%202%282%29%2B1%20%2B%20%28%28-2%29%5E2%2B2%28-2%29%20%2B%201%29%5C%5Cf%282%29%20%2B%20g%28-2%29%20%3D%205%20%2B%20%284-4%2B1%29%5C%5Cf%282%29%20%2B%20g%28-2%29%20%3D%205%20%2B1%20%3D%206)
Answer:
Step-by-step explanation:
8weeeks bc 22.50*8=180